Characteristics of successful changes in health care organizations: an interview study with physicians, registered nurses and assistant nurses - Per Nilsen; Ida Seing; Carin Ericsson; Sarah A. Birken; Kristina Schildmeijer (BMC, 2020)
Abstract Background Health care organizations are constantly changing as a result of technological advancements, ageing populations, changing disease patterns, new discoveries for the treatment of diseases and political reforms and policy initiatives. Changes can be challenging because they contradict humans' basic need for a stable environment. The present study poses the question: what characterizes successful organizational changes in health care? The aim was to investigate the characteristics of changes of relevance for the work of health care professionals that they deemed successful. Methods The study was based on semi-structured interviews with 30 health care professionals: 11 physicians, 12 registered nurses and seven assistant nurses employed in the Swedish health care system. An inductive approach was applied using questions based on the existing literature on organizational change and change responses. The questions concerned the interviewees' experiences and perceptions of any changes that they considered to have affected their work, regardless of whether these changes were "objectively" large or small changes. The interviewees' responses were analysed using directed content analysis. Results The analysis yielded three categories concerning characteristics of successful changes: having the opportunity to influence the change; being prepared for the change; valuing the change. The interviewees emphasized the importance of having the opportunity to influence the organizational changes that are implemented. Changes that were initiated by the professionals themselves were considered the easiest and were rarely resisted. Changes that were clearly communicated to allow for preparation increased the chances for success. The interviewees did not support organizational changes that were perceived to be implemented unexpectedly and/or without prior communication. They conveyed that it was important for them to understand the need for and benefits of organizational changes. They particularly valued and perceived as successful organizational changes with a patient focus, with clear benefits to patients. Conclusions Organizational changes in health care are more likely to succeed when health care professionals have the opportunity to influence the change, feel prepared for the change and recognize the value of the change, including perceiving the benefit of the change for patients.